IMPLEMENTASI DIPLOMASI KEBUDAYAAN UNI EROPA TERHADAP INDONESIA MELALUI FESTIVAL FILM EUROPE ON SCREEN PADA TAHUN 2019-2020 - M. Nur Rahman Dasnita; Yusnarida Eka Nizmi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The following study explored European Union’s cultural diplomacy practices towards Indonesia through Europe on Screen Film Festival. The existence of the European Union as an international actor that oversees many of its member states opens up many cultural products that can be used in their cultural diplomacy practices. The European Union implemented one of its cultural diplomacy agendas towards Indonesia through the Europe on Screen film festival. Therefore, this study aims to analyze the implementation of cultural diplomacy practices carried out by the European Union towards Indonesia through the Europe on Screen Film Festival in 2019 and 2020. This study used Constructivism as a perspective, Soft Power Theory, and the concept of Cultural Diplomacy. Data were gathered using qualitative approach and were found in books, academic publications, public documents, and digital archives. This research shows that the cultural diplomacy practices carried out by the European Union towards Indonesia through the Europe on Screen Film Festival in 2019 and 2020 have implemented three principles of cultural diplomacy. The Europe on Screen Festival has successfully become an event that attracts the enthusiasm of public in Indonesia, although there is no clear perception and stigma towards the European Union as institution and its existence as an international actor. Keyword: Cultural Diplomacy, Film, Festival, European Union, Europe on Screen.